Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5603/kp.a2015.0238
|View full text |Cite
|
Sign up to set email alerts
|

Is plasma-soluble CD36 associated with density of atheromatous plaque and ankle–brachial index in early-onset coronary artery disease patients?

Abstract: A b s t r a c tBackground: CD36 is a major macrophage scavenger receptor for oxidised low-density lipoprotein particles. Soluble CD36 (sCD36) is circulating as a ligand-bound complex and may be present in microparticles shed from cells such as platelets, monocytes/macrophages, or adipocytes. Positive association of plasma sCD36 with insulin resistance has been reported, and it has been proposed that sCD36 might represent a marker of macrophage activation and inflammation leading to atherosclerosis. Recently we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…The atherosclerotic plaques analysed in that study differ from those of subjects in our study in that the latter were asymptomatic and that none of the plaques were stenotic in patients with early onset (<50 years) clinically stable coronary artery disease. In line with our findings, Rac et al found no relationship between sCD36 concentrations and radiological parameters of atherosclerosis (cIMT and plaque) [33]. Finally, discordant results have been reported on the association between sCD36 concentrations and the risk of incident CV events.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The atherosclerotic plaques analysed in that study differ from those of subjects in our study in that the latter were asymptomatic and that none of the plaques were stenotic in patients with early onset (<50 years) clinically stable coronary artery disease. In line with our findings, Rac et al found no relationship between sCD36 concentrations and radiological parameters of atherosclerosis (cIMT and plaque) [33]. Finally, discordant results have been reported on the association between sCD36 concentrations and the risk of incident CV events.…”
Section: Discussionsupporting
confidence: 86%
“…This could suggest a possible protective role of higher sCD36 concentration against subclinical carotid atherosclerosis in nondiabetic subjects. A recent study reported a possible protective effect of sCD36 concentration against metabolic syndrome components in patients with early coronary artery disease [30]. Several studies have analysed sCD36 concentrations in subjects with different atherosclerotic measures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported the protective role of the CD36 polymorphism, G573A, in plaque thickness in patients with early coronary artery disease [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Ox-LDL induces the expression and release of inflammatory modulators, leading to promotion of monocyte migration, increased density of macrophage scavenger receptors, and increased uptake of ox-LDL during foam cells formation [74] , [75] ( Fig. 3 ).…”
Section: Indirect Role Of Ros In Atherosclerosismentioning
confidence: 99%